Linear Body Measurement of Indonesian Etawah Crossbred Goat [Capra aegagrus hircus (Linnaeus, 1758)] and Its Relationship with Milk Production Ability: Linear Body Measurement and Milk Production of Indonesian Crossbred Goat - Winaya, Aris; Prihartini, Indah; Ramadhan, Said Wandy; Adhim, Achmad Toat Faizal; Rico, Maria Jose Izquerdo (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Indonesian Etawah crossbred goat [Capra aegagrus hircus (Linnaeus, 1758)] was crossbred between Indonesian local goat, namely Kacang, and Etawah, imported from Jamnapari, India. Alhough Etawah goat is for dual-purpose, its milk production is high enough. The purpose of this study was to obtain information on genetic variation and genetic potential of the Indonesian Etawah crossbred goat based on linear body measurements of this goat. This study also aimed at investigating milk production ability of the goat in relation to its body measurements. This study comprised of 100 heads of Etawah crossbred goat kept by the farmers. The linear body measurement variables included body length (BL), body height (BH), chest girth (CG), udder circumference (UC) and body weight (BW). The average milk production of goat was 2.92 L/head. The linear body measurements of goat were related to milk production (r = 0.33); udder circumference had maximum influence on milk production. Thus, to improve genetic potential for milk production, the selection of goat based on udder circumference would be desirable.